DIVERSIFIKASI PENDAPATAN DAN KORUPSI TERHADAP PROFITABILITAS PERBANKAN DI NEGARA ASEAN TAHUN 2010-2021 - Sandy, Audia; Wasiaturrahma, Wasiaturrahma (LPPM STIE Muhammadiah Bandung, 2024)
The ASIAN financial crisis that occurred had an impact on the banking sector in ASEAN countries, thus encouraging the banking sector to create innovations, modify strategies and follow technological developments in order to have a competitive advantage and be able to compete with other banks. Banks diversify their income to avoid risks and increase revenue. However, diversification can be affected by high corruption in a country. The purpose of this study is to determine the impact of revenue diversification and corruption on the acquisition of profitability levels in banks. This research is a quantitative study using dynamic panel data estimated with the Sys-GMM One-Step. The results of this study indicate that revenue diversification, gross domestic product and inflation have a positive and significant effect on banking profitability in ASEAN 6. Whereas the corruption variable has a negative and significant effect on banking profitability on the ROA side and does not effect on the ROE side. Meanwhile, the corruption control variable does not significantly effect on banking profitability in ASEAN 6. Keywords: revenue diversification, corruption, banking profitability